EFEKTIVITAS UNDANG UNDANG NOMOR 7 TAHUN 2014 TENTANG PERDAGANGAN TERHADAP PENJUALAN BAHAN KIMIA BERBAHAYA - Sinaga, Cici Ariani; Ukas, Ukas (LPPM Universitas Putera Batam, 2025)
This research discusses the assessment of the effectiveness of Law No. 7/2014 on trade, in the context of the sale in context selling of hazardous chemicals with things on the distribution in hard water sales circulating among the public. Weak supervision of sales, potential misuse, and non-compliance of business actors with regulations will have a significant negative impact on society. This study aims to measure whether Law Number 7 of 2014 has been effective in supervising the sale of hazardous chemicals. This research uses a normative juridical approach method, using a literature study, which includes various sources such as books, online media, dissertations, and other relevant literature. The results show that the implementation of Law No. 7/2014 has not run optimally and has not provided a strong foundation in the supervision of hazardous chemicals due to the lack of technical guidelines and unclear authority between institutions in supervision. In addition, there are no strict regulations regarding closed distribution systems or special records of sales of hazardous chemicals such as hard water. As a result, law enforcement is weak and vulnerable to abuse. To ensure the distribution of hazardous chemicals is carried out safely and in accordance with legal provisions, this study suggests the development of more specific derivative regulations, harmonization of related laws, and greater cooperation between the government and business actors.